1981
DOI: 10.1159/000194355
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Characteristics in Chronic Obstructive Lung Disease as Related to Cardiac Size

Abstract: The hemodynamic adaptation during exercise was evaluated in 19 patients suffering from chronic obstructive lung disease. They were divided into two groups according to cardiac size on the X-ray (group 1, small; group 2, normal). A small cardio-thoracic ratio could be correlated with ‘emphysema’ assessed on the basis of hyperinflation and a low transfer test for CO. No clear-cut difference could be found between the two groups concerning the hemodynamic data at rest or during exercise. However, for all subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Although no previous publications have used dynamic-ventilation CT to observe heart size, “small heart in severe emphysema or COPD” has been observed in previous studies using different imaging modalities, including echocardiography, radiography, and magnetic resonance imaging (MRI). 9 11 , 15 , 32 , 33 The smaller heart size in patients with COPD is associated with lung hyperinflation. In patients with COPD, lung hyperinflation is caused by a decrease in the elastic recoil of the lung parenchyma and dynamic air trapping during successive breaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no previous publications have used dynamic-ventilation CT to observe heart size, “small heart in severe emphysema or COPD” has been observed in previous studies using different imaging modalities, including echocardiography, radiography, and magnetic resonance imaging (MRI). 9 11 , 15 , 32 , 33 The smaller heart size in patients with COPD is associated with lung hyperinflation. In patients with COPD, lung hyperinflation is caused by a decrease in the elastic recoil of the lung parenchyma and dynamic air trapping during successive breaths.…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 , 34 Increased intrathoracic pressure decreases venous return to the heart, which decreases cardiac preload, and impairs the compliance of the intrathoracic vascular bed. 9 11 , 16 , 17 Furthermore, external compression from hyperinflated lungs increases end-diastolic pressure. 10 , 15 , 35 Consequently, cardiac size and function is compromised in patients with COPD and/or severe emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the size of the lungs due to hyperinflation has a compression effect on the heart muscle, creating unfavorable conditions for its activity and hindering the implementation of its pumping function. A number of studies have shown that an increase in the severity of COPD and the appearance of emphysema are associated with a decrease in the size of the heart during X-ray examination (32)(33)(34). Almost 40 years ago, the term "microcardia" was widely used, and was considered a radiological sign of emphysema (33).…”
Section: Effect Of Lung Hyperinflationmentioning
confidence: 99%
“…Увеличение размеров легких вследствие гипервоздушности оказывает компрессионное воздействие на сердечную мышцу, создавая неблагоприятные условия для ее деятельности и затрудняя осуществление ею насосной функции. В ряде исследований было показано, что повышение тяжести ХОБЛ и появление эмфиземы связано со снижением размеров сердца при рентгенологическом исследовании [33][34][35]. Почти 40 лет назад был широко распространен термин -микрокардия, который считался рентгенологическим признаком эмфиземы [34].…”
Section: влияние гипервоздушности (гиперинфляции) легкихunclassified